Analisis Pengaruh Day of The Week Effect terhadap Return Saham di Bursa Efek Jakarta - Arum Indrasari; Afrizal Tahar (Journal of Accounting and Investment, 2004)
Some of the people have believed in the superstitions in which there exists “good days” for doing  activities, including to start business and investment. The purpose of this paper is to disclose to what extent the phenomenon of market anomaly is feasible in Jakarta Stock Exchange in connection to the existence of the effect of “good days” for trading on daily stock returns. Based on the research result, we found the there exist distinction in daily stock return and abnormal returns particularly on Tuesday and Wednesday.